Mempelajari misteri ilmu khidir Dalam era millenial (Analisis Kontroversi Gus Dur Perspektif Ilmu Khidir) - Ahmad Ahmad (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
Calling Gus Dur's name must have crossed the Ulama ', Nation's Teachers, thinkers. However, the figure of Gus Dur cannot be separated from his thoughts which are often controversial and eccentric. One of them was Gus Dur's thought to revoke the Standing Regulations of the People's Consultative Assembly Number XXV in 1966 concerning the dissolution of the Indonesian Communist Party, the statement as a prohibited organization throughout the Republic of Indonesia for the Indonesian Communist Party and prohibition of any activities to disseminate or develop ideas or teachings communism / Marxism-Leninism. This thinking is not only controversy and eccentric, but also invites strong reactions from the people themselves, the scholars. In a different frame and context, the controversy that is similar to Gus Dur's thought ever happened and enshrined in the Qur'an, namely the story of the Prophet Khidr and Prophet Moses. In the horizon of thought, Gus Dur basically "just" explained the knowledge that was known and other people did not know it. Likewise, Prophet Khidir when 'giving lessons' to the Prophet Moses. Prophet Khidir ‘only’ explained what was known while the Prophet Moses did not know it.